Desain dan pembuatan pakaian kerja kulit - Widiarti, Th (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1999)
The preparation of leather custom for hard workersÂ was aimed to increase the diversification of leather good products garment, to obtain a practical and simple method of leather garment preparation, as well as to seek suitable fashion of hard workers wear.Eight designs prepared, of leatherÂ costum for hard workers followed Â by selection of the most favourite designs by ten panelists. Based on the selected designs, the leatherÂ costum were then prepared. The manufacturing of the leather garment was carried â out in sequence of the following works, basic pattern preparation performed in mass production system, in standard size, material cutting, preparation for assembling and stitching. Three pieces of leather garment for hard workers were produced in size 48 (M) for this purpose, where as the most favourite designs were 1, 2 and 3. Leather garment for hard workers of designs one, two and three met good marks, while design 1 was fair. Technology of manufacturing obviously affected the quality of leather garment for hard workers, as well as the selection of the raw materials quality. The result of study could be presented as the following design one for quality of material was fair. Design two and three met good mark for the higher quality of raw material was utilized to manufacture high quality leather garment for hard workers some considerations should be taken, they are : economicalÂ use of raw material; practice simple styles; and proporsional lines and sizes. The conformity of the technical requirements will produce sound quality productsÂ INTISARIPembuatan pakaian kerja dari kulit bertujuan untuk menambah keanekaragaman garmen kulit, mencari suatu cara yang praktis dan mudah untuk membuat garment kulit. Disamping itu juga untuk mendapatkan model yang cocok untuk pakaian kerja berat.Telah dibuat delapan rancangan pakaian kerja berat dari kulit, kemudian diadakan pemilihan rancangan yang paling disukai oleh sepuluh orang panelis. Berdasarkan hasil pemilihan rancangan, kemudian dibuat pakaian kerja dari kulit dalam bentuk prototip Proses pembuatannya meliputi pembuatan pola dasar dengan system ukuran standar, pemotongan bahan, preparasi dan penjahitan. Hasil yang dicapai adalah tiga potong pakaian kerja berat dari kulit dengan ukuran 48 (M), sedangkan modelÂ yang disukai adalah Gambar 1., Gambar 2. Dan Gambar 3., sesuai dengan rancangan yang terpilih. Prototip yang dibuat dinilai oleh sepuluh orang panelis dengan hasil : pakaian kerja gambar rancangan dua dan tiga dinilai baik, sedangkan nomor satu cukup baik. Hasil penilaian menunjukkan Gambar 1. Cukup baik, karena mutu bahan dasar yang dipilih bermutu cukup. Sedangkan pakaian kerja Gambar 2. dan Gambar 3., hasilnya baik karena mutu bahan dasarnya baik. Dengan terpenuhinya persyaratan teknis, maka hasil produksi yang bermutu baik akan tercapai.